Cost Effectiveness Analysis of Eribulin Mesylate as a Treatment for Metastatic Breast Cancer in Spain: Management in the Later Line of Therapy - Gabriel Tremblay; Unnati Majethia; Ilias Kontoudis; Jesús De Rosendo (Journal of Health Economics and Outcomes Research)
**Background:** Two thirds (62%) of metastatic breast cancer (MBC) patients in Western Europe have human epidermal growth factor receptor 2 (HER2)-negative disease, for which anthracyclines and taxanes are recommended as first-line treatments, followed by microtubule-targeting agents such as capecitabine, vinorelbine and/or eribulin. The study objective was to compare the cost-effectiveness of eribulin in Spain as a second-line treatment for HER2-negative MBC with its current status as a third-line treatment for patients who have received capecitabine.